Legal Protection of Kurash Athletes' Rights in Indonesia - Ananda Triputra Rizki Sumadi; Fokky Fuad (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The legal protection of Kurash athletes’ rights is a shared responsibility between the central and regional governments. Guarantees regarding decent income, health insurance, career advancement, appreciation, and performance bonuses must be optimized and distributed fairly to all Kurash athletes. This study aims to examine the extent of the implementation of Law No. 11 of 2022 on Sports and related regulations, as well as to identify obstacles in fulfilling athletes’ rights. The research applies a juridical-empirical method with descriptive analysis, analyzing Law No. 11 of 2022 and collecting data through interviews with relevant informants. The findings reveal that although regulations protecting athletes’ rights exist, the implementation of legal protection for Kurash athletes remains suboptimal. The inhibiting factors include budget constraints, limited government attention to non-Olympic sports, and the persistence of corruption among certain organizational officials. This study emphasizes the importance of collaboration between the government, sports organizations, and society to create a fair and sustainable ecosystem for the development of Kurash athletes.